2007
DOI: 10.1007/s11069-007-9146-x
|View full text |Cite
|
Sign up to set email alerts
|

The storage potential of different surface coverings for various scale storms on Wu-Tu watershed, Taiwan

Abstract: An impervious surface cover is continuously spreading over the Wu-Tu upstream watershed due to the concentrated population and raised economical demands, while that area also frequently suffers from heavy storms or typhoons during the summer season. The increased flood volume due to this extended imperviousness causes a greater potential hazard than that of the past. In order to evaluate the urbanized impacts on the watershed, a set of methods were used to estimate the changes of the watershed storage. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Thus, the hydrographical characteristics of a developed watershed vary in conjunction with the degree of urbanization (Kliment and Matoušková 2009). Previous studies have shown that the affected factors include rainwater loss (Gremillion et al 2000, Cheng et al 2008b, watershed function (Krug 1996, Kang et al 1998, Aronica and Cannarozzo 2000, Cheng and Wang 2002, surface runoff (Boyd et al 1994, Junil et al 1999, Rodriguez et al 2003, runoff volume (Arnell 1982), peak discharge (Huang et al 2008a(Huang et al , 2008b, time to peak (Huang et al 2012) and baseflow (Simmons and Reynolds 1982). However, the hydrological effects of urbanization may be particularly severe in watershed divisions that are vulnerable to the breaking of links in the hydrological cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the hydrographical characteristics of a developed watershed vary in conjunction with the degree of urbanization (Kliment and Matoušková 2009). Previous studies have shown that the affected factors include rainwater loss (Gremillion et al 2000, Cheng et al 2008b, watershed function (Krug 1996, Kang et al 1998, Aronica and Cannarozzo 2000, Cheng and Wang 2002, surface runoff (Boyd et al 1994, Junil et al 1999, Rodriguez et al 2003, runoff volume (Arnell 1982), peak discharge (Huang et al 2008a(Huang et al , 2008b, time to peak (Huang et al 2012) and baseflow (Simmons and Reynolds 1982). However, the hydrological effects of urbanization may be particularly severe in watershed divisions that are vulnerable to the breaking of links in the hydrological cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall-runoff modelling with IUHs has been studied by O'Connell and Todini (1996), Melone et al (1998), Bhadra et al (2010) and others. Furthermore, the changes in hydrograph characteristics on an urbanized watershed have also been evaluated by identifying the relationships between IUH parameters and urbanization variables (Cheng and Wang 2002, Cheng et al 2008b, Huang et al 2008a, Kliment and Matoušková 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrologists acknowledge that urbanization in a basin leads to growth of impervious paving and prevents rainwater from accessing the land surface (Chow et al 1988). The part of a watershed contributing to surface runoff has been found to be proportional to the impervious areas (Brown 1988;Boyd et al 1994;Arnold and Gibbons 1996;Matheussen et al 2000;Cheng et al 2008b).…”
Section: Introductionmentioning
confidence: 99%